Polymer-derived SiOC as support material for Ni-based catalysts: CO2 methanation performance and effect of support modification with La2O3 - Szoldatits, E.; Essmeister, J.; Schachtner, L.; Konegger, T.; Föttinger, K. (Frontiers in Chemistry, 2023)
In this study, we investigated Ni supported on polymer-derived ceramics as a new class of catalyst materials. Catalysts have to withstand harsh reaction conditions requiring the use of a support with outstanding thermal and mechanical stability. Polymer-derived ceramics meet these requirements and bring the additional opportunity to realize complex porous structures. Ni-SiOC and La-modified Ni-SiOC catalysts were prepared by wet impregnation methods with target concentrations of 5 wt% for both metal and oxide content. Polymer-derived SiOC supports were produced using a photoactive methyl-silsesquioxane as preceramic polymer. Catalysts were characterized by N2-adsorption-desorption, XRD, SEM, H2-TPR, and in-situ DRIFTS. CO2 methanation was performed as a test reaction to evaluate the catalytic performance of these new materials at atmospheric pressure in the temperature range between 200-400 °C. XDR, H2-TPR, and in-situ DRIFTS results indicate both improved dispersion and stability of Ni sites and increased adsorption capacities for CO2 in La-modified samples. Also, modified catalysts exhibited excellent performance in the CO2 methanation with CO2 conversions up to 88 % and methane selectivity >99 % at 300 °C reaction temperature. Furthermore, the pyrolysis temperature of the support material affected the catalytic properties, the surface area, the stability of active sites, and the hydrophobicity of the surface. Overall, the materials show promising properties for catalytic applications.